Research on Flood Control and Drainage Simulation of Artificial Water Networks Based on SWMM Coupled with HEC-RAS - XIA Minghui; YIN Shiyang (Renmin Zhujiang)
Accurate simulation and analysis of hydrology and hydraulic processes in newly constructed urban areas are crucial for the planning and construction of artificial water networks and the prevention of flooding in newly constructed urban areas. A distributed hydrological model of SWMM was coupled with a two-dimensional hydrodynamic model (SWE-ELW) of HEC-RAS to simulate and analyze flood control and drainage in the southern water network of Fuyang City in Anhui Province. The results show that the number of calculation parameters in the SWMM model is more, and the drainage modulus decreases with increasing catchment area, which is close to the drainage modulus in planned pump stations, making the calculation results more reasonable. Under the condition of a 30-year return period of the southern water network drainage standard, the highest water level in the southern water network reaches 27.89 m during flood season, meeting the requirements of the drainage scheme. The flow through each gate is proportional to the river channel's bottom width, and the fluctuation degree of each process line of each gate is inversely proportional to the river channel's bottom width. The network first stores water before discharging it, reducing peak flow by 57.21 m3/s, delaying peak flow by 2.83 hours, storing flood by 1.69 million m3, and reaching a peak flow reduction rate of 42.45%, resulting in significant flood control and drainage benefits. This method has certain simulation effects and accuracy, which can provide reference and guidance for related studies on flood control and drainage in artificial water network construction.